2011
DOI: 10.1016/j.bbamcr.2011.07.017
|View full text |Cite
|
Sign up to set email alerts
|

The survival effect of mitochondrial Higd-1a is associated with suppression of cytochrome C release and prevention of caspase activation

Abstract: Higd-1a (hypoxia induced gene domain family-1a) is a mitochondrial inner membrane protein with a conformation of N-terminal outside-C-terminal outside and loop inside. There are four Higd genes, Higd-1a, -1b, -1c and -2a, in the mouse. Higd-1a and -2a are expressed primarily in the brain, heart, kidney and leukocytes. HIF (hypoxia-inducible factor) overexpression induced the endogenous expression and promoter activity of Higd-1a. Mutation of the HRE (hypoxia-response element) site at -32bp in the Higd-1a promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…Although it is induced by hypoxia and promotes survival, its modes of action remain to be clarified. We showed that Higd-1a-transfected cells underwent significantly less apoptosis, as the result of inhibition of the release of cytochrome c and reduction of caspase activities (22). In the present study, we found that Higd-1a protects the Opa1 L isoform from induced cleavage.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…Although it is induced by hypoxia and promotes survival, its modes of action remain to be clarified. We showed that Higd-1a-transfected cells underwent significantly less apoptosis, as the result of inhibition of the release of cytochrome c and reduction of caspase activities (22). In the present study, we found that Higd-1a protects the Opa1 L isoform from induced cleavage.…”
supporting
confidence: 56%
“…Wang and coworkers showed that such apoptosis was inhibited by ectopic expression of Higd-1a in pancreatic β cells (18,36). We have shown that hypoxia-induced apoptosis can be prevented by overexpression of Higd-1a in RAW264.7 macrophages (22).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations